Microfluidic Chip for Trapping Magnetic Nanoparticles and Heating in Terms of Biological Analysis - Le Ngoc, Tu; Nguyen Cong, Thinh; Tran, Lam Dai; Nguyen, Van-Anh; Cao Hong, Ha (Communications in Physics, 2020)
In this study, we reported the results of the design and the fabrication a planar coil in copper (square, a = 10 mm, 15mm high, 90 turns), these planar coils were integrated in a microfluidic chip for trapping magnetic nanoparticles and local heating applications. A small thermocouple (type K, 1 mm tip size) was put directly on top of the micro-channel in poly(dimethyl-siloxane) in order to measure the temperature inside the channel during applying current. The design of planar coils was based on optimizing the results of the magnetic calculation. The most suitable value of the magnetic field generated by the coil was calculated by ANSYS® software corresponded to the different distances from the coil surface to the micro-channel bottom (magnetic field strength Hmax = 825 A/m). The magnetic filed and heating relationship was balanced in order to manipulating the trapping magnetic nanoparticles and heating process. This design of the microfluidic chip can be used to develop a complex microfluidic chip using magnetic nanoparticles.